MODEL DISTRIBUSI GULA KELAPA YANG OPTIMAL - Nikmatul Khoiryah; Masyhuri Masyhuri; Amul Jadidah (Fakultas Pertanian Universitas Yudharta Pasuruan, 2011)
ABSTRACT: Distribution channel has a great influence in marketing a certain product. It has become a serious problem faced by the entrepreneur of brown sugar in Nglegok district, Blitar. Not a few of them have a financial loss due to the fact that the product is not distributed efficiently. This research is aimed at knowing about the distribution channel of brown sugar optimally that which is suitable to the selling target. In addition, it is also aimed at detecting the network of brown sugar market.This research is a quantitative descriptive research using a transport method which applies both an analysis of NWCR (North West Corner Method), MODI (Modified Distribution Method) and a network analysis. From the analysis of NWCR Initial Solution for the distribution channel it is known that an is optimal distribution channel has the amount of Rp. 6.938.166. The distribution channel, which is appropriate to the selling target is indicated by recommendation of allocation in distributing brown sugar for distributor II as much as 10.500 kg/week to Pare, 13.300 kg/week to Jombang, and 700 kg/week to Tulungagung, to the distributor III as much as 2800 kg/week to Tulungagung and 1200 kg/week to Tuban. The allocation in distributing brown sugar for the distributor IV is as much as 1400 kg/week to Babat, 4600, 70 kg/week to Surabaya, 2300, 30 kg/week to Talun and 2000 kg/week to Batu. Therefore, the optimal solution for the channel distribution by MODI analysis is Rp. 773.314. Absolutely, the amount is by recommendation of allocation in distributing brown sugar to the channel distribution that is proper to the target market as much as 700 kg/week to Pare and 800 kg/week to Jombang for the distributor I, for the distributor II is 1000 kg/week to Wlingi, 500 kg/week to Kesamben, 5800 kg/week to Pare, 3500 kg/week to Tulungagung, 1200 kg/week to Tuban, 1400 kg/week to Babat, 4600,70 kg/week to Surabaya, 2300, 30 kg/week to Talun and 2000 kg/week to Batu, for the distributor III, is 4000 kg/week to Pare, and for the distributor IV is 12500 kg/week to Jombang. The network marketing, which supports the distribution of sugar brown, is indicated by varying route of shortest shipping to the distribution channel aimed. From the analysis, Pare becomes the alternative place for the shipping of brown sugar.